Analisis Pengaruh Faktor-faktor Fundamental terhadap Harga Saham pada Perusahaan Manufaktur di Bursa Efek Indonesia (BEI) - Dermawan Wijaya (Universitas Tarumanagara, 2022)
This research aims to analyze the effect of fundamental factors on stock price in manufacturing companies which are listed in the Indonesia Stock Exchange. Fundamental factors that become this research objects are current ratio (CR), debt to equity (DER), return to equity ratio (ROE), total assets turnover (TATO) and earning per share (EPS) as independent variables, while stock price becomes dependent variables. The research subjects are manufacturing companies listed in Indonesia stock Exchange between period of 2013-2016 and have published profitable financial statements. Sampling method used is purposive sampling and the analysis method used is panel data regression. The research model selected is fixed effect model (FEM). The result shows that CR, DER, ROE, TATO and EPS has significant and simultaneous effects on stock price. Where only ROE and EPS has significant and partial effect on stock price. This study concludes that not all independent variables have significant effect on stock price.